A Sociological Analysis for Factors Affecting the Attitude toward Childbearing (Case Study: Employees of Andimeshk Department of Education) - Eshagh Arjmand Siahpoush; Mehdi Zeini Wendian; Daryoush Rezapour (توسعه اجتماعی, 2021)
Childbearing as one of the components of demographic change is one of the topics that have attracted a lot of attention in the field of social issues. Due to the importance of demographic developments in Iran in the past decades, the current research aims to identify the factors affecting the attitude toward childbearing among the employees of Andimeshk Department of Education. As a survey research, it used a researcher-made questionnaire for data collection. The statistical population included all employees of Andimeshk Department of Education, out of which a total of 362 individuals was selected using the Cochran formula by adopting and simple random sampling. The data analysis was done using SPSS 18. The results showed a negative correlation between the level of education and the attitude toward childbearing but a positive correlation between the variables of the inclination toward material welfare and attention to maternal health with childbearing. The results of the regression analysis also indicated that independent variables account for 16.9% of changes in the attitude toward childbearing and have the biggest effect on the variables of the inclination toward material welfare and the level of education.